Implikasi Moral Hazart dalam Pemilu Legislatif Serentak 2024 - Raihan Dara Vonna; Muhammad Rayyan Abyan (Bulletin of Community Engagement, 2024)
In the context of elections, moral hazard can take the form of ethical violations committed by election organizers, candidates, or citizens who take part in the election process. Moral hazard in the electoral context refers to a situation where political actors or voters take higher risks because they know that the consequences will be borne by other parties. This study find out the Hazart's Moral Implications for the 2024 Simultaneous Legislative Elections. The researchers used normative juridical approach. The result shows that the practice of moral hazard in the 2024 Simultaneous Elections in Indonesia could have very serious implications for the integrity and legitimacy of the election results. If fraudulent practices such as money politics, data manipulation and negative campaigns cannot be prevented and dealt with effectively, the democratic process in Indonesia could be distorted.